2017
DOI: 10.1186/s12939-017-0575-1
|View full text |Cite
|
Sign up to set email alerts
|

Measuring inequalities in the distribution of the Fiji Health Workforce

Abstract: BackgroundDespite the centrality of health personnel to the health of the population, the planning, production and management of human resources for health remains underdeveloped in many low- and middle-income countries (LMICs). In addition to the general shortage of health workers, there are significant inequalities in the distribution of health workers within LMICs. This is especially true for countries like Fiji, which face major challenges in distributing its health workforce across many inhabited islands.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 24 publications
0
27
1
Order By: Relevance
“…The application of strict inclusion and exclusion criteria in this study combined with known inequity in access to healthcare services and distribution of the health workforce in Fiji, particularly for patients in rural and remote areas and those requiring specialist medical services, means this study may underestimate the true burden of ESKD …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of strict inclusion and exclusion criteria in this study combined with known inequity in access to healthcare services and distribution of the health workforce in Fiji, particularly for patients in rural and remote areas and those requiring specialist medical services, means this study may underestimate the true burden of ESKD …”
Section: Discussionmentioning
confidence: 99%
“…The application of strict inclusion and exclusion criteria in this study combined with known inequity in access to healthcare services and distribution of the health workforce in Fiji, particularly for patients in rural and remote areas and those requiring specialist medical services, means this study may underestimate the true burden of ESKD. [33][34][35] Conclusion ESKD is a rapidly growing global problem and there has been a paucity of data about this condition from the developing countries of the Western Pacific. 36 This study from Fiji, the largest of the developing nations in this region, concludes that the incidence of ESKD and associated mortality in Fiji is very high.…”
Section: Eskd In Fijimentioning
confidence: 99%
“…This result is mainly due to the population‐oriented allocation policy of health workforces. Most health resource planning programs, including programs raised by WHO, regard population size as the most important factor . Few consider geographical area and other influencing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Then, Munga and Maestad [63] found significant inequalities in the distribution of health workers in Tanzania. Wiseman et al [64] conducted research in Fiji and found greater inequalities in the density of health workers at the provincial level compared to divisional level. Also, inequities in the distribution of healthcare workers were found in Cameroon by Tandi et al [65].…”
Section: Theory Background and Literature Reviewmentioning
confidence: 99%